Arsenic-fluoride co-exposure induced endoplasmic reticulum stress resulting in apoptosis in rat heart and H9c2 cells. (February 2022) - Li, Meng; Feng, Jing; Cheng, Ying; Dong, Nisha; Tian, Xiaolin; Liu, Penghui; Zhao, Yannan; Qiu, Yulan; Tian, Fengjie; Lyu, Yi; Zhao, Qian; Wei, Cailing; et al.
Abstract: Exposure to arsenic (As) or fluoride (F) has been shown to cause cardiovascular disease (CVDs). However, evidence about the effects of co-exposure to As and F on myocardium and their mechanisms remain scarce. Our aim was to fill the gap by establishing rat and H9c2 cell exposure models. We determined the effects of As and/or F exposure on the survival rate, apoptosis rate, morphology and ultrastructure of H9c2 cells; in addition, we tested the related genes and proteins of endoplasmic reticulum stress (ERS) and apoptosis in H9c2 cells and rat heart tissues. The results showed that As and/or F exposure induced early apoptosis of H9c2 cells and caused endoplasmic reticulum expansion. Additionally, the mRNA and protein expression levels of GRP78, PERK and CHOP in H9c2 cells were higher in the exposure groups than in the control group, and could be inhibited by 4-PBA. Furthermore, we found that As and/or F exposure increased the expression level of GRP78 in rat heart tissues, but interestingly, the expression level of CHOP protein was increased in the F and As groups, while significantly decreased in the co-exposure group. Overall, our results suggested that ERS-induced apoptosis was involved in the damage of myocardium by As and/or F exposure. In addition, factorial analysis results showed that As and F mainly play antagonistic roles in inducing myocardial injury, initiating ERS and apoptosis after exposure. Graphical abstract: Image 1 Highlights: Arsenic-fluoride induced early apoptosis of H9c2 cells and caused endoplasmic reticulum expansion. Arsenic-fluoride increased the levels of GRP78 protein in rat myocardium and H9c2 cells. Arsenic-fluoride promoted apoptosis by activating endoplasmic reticulum stress. Under this experimental condition, arsenic and fluoride mainly exhibited antagonistic effects on myocardial injury, endoplasmic reticulum stress and apoptosis.